THE EFFECT OF STUDENT WORKSHEETS BASED ON PROBLEM SOLVING ON STUDENTS' CRITICAL THINKING ABILITY IN CLASS XI SMA ON DYNAMIC FLUID MATERIALS - Rahmaddillah Al Fath; Wahyuni Satria Dewi (Universitas Negeri Padang, 2022)
The 2013 curriculum is now being implemented by the government. The goal of the 2013 curriculum is for pupils to have 4C and HOTS competencies. HOTS accomplishment indicators can be seen in relation to 4C abilities, which demand critical thinking from pupils. Students' mindsets will be trained to deal with complicated challenges by developing critical thinking abilities. However, real-world situations in schools demonstrate that pupils' critical thinking skills are still relatively low; the reason for this is that the 2013 curriculum has not been applied adequately in schools. As a result, the solution to this problem is to use problem-solving-based Student Worksheets as instructional resources in the learning process. The purpose of this study is to see how using problem-solving-based Student Worksheets on dynamic fluid content for class XI SMA affects students' critical thinking skills.Post-test Only, Non-Equivalent Control Group Design is a quasi-experimental research design used in this study. For the purpose of this study, the population consisted of students in class XI Natural Sciences. The example used is from class XI (Natural Sciences 1 and 2). This study just looks at the aspect of knowledge. Normality, homogeneity, and hypothesis testing were used to examine the research data at a significance level of 0.05..Based on the findings of the data analysis, it can be determined that the Problem Solving Model Student Worksheet has a stronger impact on critical thinking abilities in class XI Natural Sciences 2 than in class XI Natural Sciences 1.